2021
DOI: 10.3389/fmolb.2021.723003
|View full text |Cite
|
Sign up to set email alerts
|

PROLIDASE: A Review from Discovery to its Role in Health and Disease

Abstract: Prolidase (peptidase D), encoded by the PEPD gene, is a ubiquitously expressed cytosolic metalloproteinase, the only enzyme capable of cleaving imidodipeptides containing C-terminal proline or hydroxyproline. Prolidase catalyzes the rate-limiting step during collagen recycling and is essential in protein metabolism, collagen turnover, and matrix remodeling. Prolidase, therefore plays a crucial role in several physiological processes such as wound healing, inflammation, angiogenesis, cell proliferation, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 194 publications
(241 reference statements)
0
42
0
Order By: Relevance
“…PEPD encodes prolidase, which catalyzes the hydrolysis of a dipeptide containing a C-terminal proline or hydroxyproline into constituent amino acids, and the most studied substrates of the enzyme are imidodipeptides, which are generated during the breakdown of collagen. It was reported that oxidative stress stimulates collagen breakdown via inductions of matrix metalloproteinases and induces inflammatory homeostasis ( Eni-Aganga et al., 2021 ). The c.151G > A mutation is harmful for the function of prolidase.…”
Section: Discussionmentioning
confidence: 99%
“…PEPD encodes prolidase, which catalyzes the hydrolysis of a dipeptide containing a C-terminal proline or hydroxyproline into constituent amino acids, and the most studied substrates of the enzyme are imidodipeptides, which are generated during the breakdown of collagen. It was reported that oxidative stress stimulates collagen breakdown via inductions of matrix metalloproteinases and induces inflammatory homeostasis ( Eni-Aganga et al., 2021 ). The c.151G > A mutation is harmful for the function of prolidase.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a comparison of our list vs. the proteome profiling in dermal myofibroblasts of patients with hEDS [ 62 ] identified only five genes. One of them, prolidase (peptidase D), encoded by PEPD , is a ubiquitously expressed cytosolic metalloproteinase essential in protein metabolism, collagen turnover, and matrix remodeling [ 63 ], representing a potential candidate to be evaluated in larger cohorts of patients with HSD. On the other hand, a key factor identified by proteomic analysis in hEDS fibroblasts was S1004A, a calcium-binding protein involved in the fibroblast-to-myofibroblast transition, supporting a proinflammatory milieu characterized by an excessive matrix metalloproteinase-mediated ECM degradation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen breakdown is carried out by sequential cleavage into dipeptides by matrix metalloproteinases [43]. The terminal and rate limiting stage of collagen degradation is catalyzed by prolidase (PEPD) [44]. This enzyme specifically splits dipeptides with C-terminal Pro or Hyp.…”
Section: Collagen Degradation and Further Metabolism Of Hypmentioning
confidence: 99%